On one inequality for the moduli of continuity of fractional order generated by semigroups of operators - Bezkryla, S. I.; Nesterenko, A. N.; Chaikovs'kyi, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
A new inequality for the moduli of continuity of fractional order generated by semigroups of operators is obtained. This inequality implies a generalization of the well-known statement that there exists an α-majorant, which is not a modulus of continuity of order α generated by a semigroup of operators, to the case of noninteger values of α.